Financial management in the public sector tools, applications, and cases - Wang, XiaoHu (Armonk, N.Y M.E. Sharpe, 2010)
The new edition of Financial Management in the Public Sector provides a step by step guide on how to use financial management and budgeting tools in the public organizations. The book features a practical, case-study approach, and includes plentiful exercises and examples. It is designed as a textbook for courses on public financial management or public budgeting that focus on the application of budgeting and financial management tools. Public service professionals will also benefit from this handy primer. Improvements and enhancements in the new edition include: A new chapter on debt capacity analysis. This chapter presents a tool that identifies the acceptable level of borrowing for the government-an urgent topic for many governments that exceed their debt capability to borrow, which can lead to financial insolvency. A new chapter on financial risk assessment. This chapter presents an important tool on how to assess financial risk posed to government and how to reduce possibilities of high-risk financial hardship and insolvency. A new appendix on Excel functions. A detailed glossary for easy identification and hook-up of key terms.
Includes bibliographical references Index.
Keywords: Finance, Public. Finance, Public-Accounting. Budget